The quest for fear : from the tale of oral tradition to albums for children - Charnay, Bochra (Ondina - Ondine, 2021)
This article attempts to identify the multiple configurations of fear in a corpus made up of tales and legends from French oral heritage and their rewritings intended for a young readership. These are mainly Breton tales and legends by François-Marie Luzel and Émile Souvestre, as well as the cycle "John without fear", frequent in all regions of France. The study highlights the mythical dimension of these stories and analyzes their evolution in transpositions for young people. Key words: Fear, tale, legend, Luzel, Souvestre, disturbing strangeness, washerwoman, ghost, Ankou.